Trends in Outdoor Recreation, Leisure and Tourism - Gartner, William C (CABI, 2014)
How will we choose to travel and recreate in 20 years time? Will we still be content to squeeze into an airline seat and endure hours of uncomfortable travel to do the things we want to do in the place where we want to do them? Will we still recreate in ways that our mentors taught us or will we find new forms of recreation to challenge our skills? Will technology enable us to travel to all the places and do all the things that we can vicariously experience now using the Internet, or will new communication and virtual reality devices substitute for old-fashioned recreation and travel? How will public and private sector providers of leisure opportunities and services adjust to the numerous forces with which they will have to contend and, often, only peripherally control? These are only some of the many questions being asked today regarding the future of recreation and tourism